PET Imaging of Neuroinflammation in Alzheimer’s Disease - Zhou, Rong; Ji, Bin; Kong, Yanyan; Qin, Limei; Ren, Wuwei; Guan, Yihui; Ni, Ruiqing (Frontiers in Immunology, 2021)
Neuroinflammation play an important role in Alzheimer’s disease pathogenesis. Advances in molecular imaging using positron emission tomography have provided insights into the time course of neuroinflammation and its relation with Alzheimer’s disease central pathologies in patients and in animal disease models. Recent single cell sequencing and transcriptomics indicate dynamic disease-associated-microglia and astrocyte profiles in Alzheimer’s disease. Mitochondrial 18kDa translocator protein is the most widely investigated target for neuroinflammation imaging. New generation of translocator protein tracers with improved performance have been developed and evaluated along with tau and amyloid imaging for assessing the disease progression in Alzheimer’s disease continuum. Given that translocator protein is not exclusively expressed in glia, alternative targets are under rapid development, such as monoamine oxidase-B, matrix metalloproteinases, colony-stimulating factor 1 receptor, imidazoline-2 binding sites, cyclooxygenase, cannabinoid-2 receptor, purinergic P2X7 receptor, P2Y12 receptor, the fractalkine receptor, triggering receptor expressed on myeloid cells 2, and receptor for advanced glycation endproducts etc. Promising targets should demonstrate a higher specificity for cellular locations with exclusive expression in microglia or astrocyte and activation status (pro-inflammatory or anti-inflammatory) with highly specific ligand to enable in vivo brain imaging. In this review we summarize recent advances in the development of neuroinflammation imaging tracers and provide an outlook for promising targets in the future.